Komitmen Dosen Universitas Negeri Malang (UM) dan Faktor-faktor yang Mempengaruhinya - Agus Timan (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2004)
The aims of this causal, comparative survey were to describe lecturers’ commitment and to examine the effects of personal, organizational, and non-organizational factors on lecturers’ commitment. Using proportional stratified random sampling, this study involved 153 lecturers of the III-rank wage scale selected out of the 513 lecturers. The data were collected through questionnaires and documents and then analyzed using correlations, multiple regression, and t-test. The findings suggest that personal and organizational factors were of good category and had positive relationship with lecturers’ commitment, whereas non-organizational factor was not as good and had no correlation with lecturers’ commitment. In general, the lecturers were highly committed and there was no difference in commitment between male and female lecturers.